Enhanced Ability of Agarwood Leaves (Aquilaria malaccensis Lam.) Ointment as Wound Healing to Heal Second-Degree Burns in Rats - Desmiaty, Yesi; Sandhiutami, Ni Made Dwi; Fahleni, Fahleni; Griselda, Agnes; Apriliana, Amalia Zahra (Sciences of Pharmacy, 2024)
Agarwood leaves (Aquilaria malaccensis Lam.) contain chemical substances such as alkaloids, flavonoids, and triterpenoids that contribute to the healing process of burns. This study aims to evaluate the wound healing activity of spray-dried extract from agarwood leaves formulated into an ointment for second-degree burns. The method involves extracting agarwood leaves through the decoction method, followed by spray drying, and subsequent evaluation of the extract. The prepared extract was then formulated into an ointment and tested for wound healing activity on 24 white rats of the Sprague-Dawley strain, divided into four groups, each consisting of 6 rats: negative control (ointment base), positive control (Betadine®), formula 1 (agarwood leaves extract ointment with 20% extract concentration - ALO-20), and formula 2 (agarwood leaves extract ointment with 30% extract concentration - ALO-30). Second-degree burns were induced by exposing the rats' backs to ferrous metal for 3 seconds and treating them for 14 days. Observations were made by assessing changes in burn diameter and scab formation. In this study, ALO-30 demonstrated superior activity. Scab formation was faster on day 3, and the burn diameter was reduced by day 7. The results indicated that ALO-30 led to a quicker reduction in wound diameter compared to ALO-20 and the negative control. Agarwood leaves extract ointment with a concentration of 30% (ALO-30) exhibited a more effective wound healing effect than the ointment with a 20% concentration (ALO-20).